2009
DOI: 10.1287/isre.1070.0164
|View full text |Cite
|
Sign up to set email alerts
|

Governance-Knowledge Fit in Systems Development Projects

Abstract: T his study addresses the theoretically underexplored question of how fit between project governance configurations, and the knowledge of specialized information technology (IT) and client departments, influences information systems development (ISD) performance. It conceptualizes project governance configurations using two classes of project decisions rights-decision control rights and decision management rights. The paper then develops a middle-range theory of how governance-knowledge fit shapes ISD performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 46 publications
(91 reference statements)
3
61
0
Order By: Relevance
“…Other studies reported higher variance between 35% and 36% from a first factor (e.g., Hess et al, 2009;Phang et al, 2009) and concluded that common method bias is not substantially present. A few studies reported 72% -76% total variance explained by all factors (Dinev and Hart, 2006;Dinev and Hu, 2007;Tiwana, 2009). In our data, we found 37.7% variance from the first factor and 77.6% total variance explained.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Other studies reported higher variance between 35% and 36% from a first factor (e.g., Hess et al, 2009;Phang et al, 2009) and concluded that common method bias is not substantially present. A few studies reported 72% -76% total variance explained by all factors (Dinev and Hart, 2006;Dinev and Hu, 2007;Tiwana, 2009). In our data, we found 37.7% variance from the first factor and 77.6% total variance explained.…”
Section: Resultssupporting
confidence: 60%
“…We examined survey studies in leading IS journals that used Harman's single-factor test and reported explained variance from factor analysis. Some studies reported 12% -18% of variance explained by a first factor (e.g., Dinev and Hart, 2006;Dinev and Hu, 2007;Pavlou and Gefen, 2004;Tiwana, 2009). Other studies reported higher variance between 35% and 36% from a first factor (e.g., Hess et al, 2009;Phang et al, 2009) and concluded that common method bias is not substantially present.…”
Section: Resultsmentioning
confidence: 99%
“…ISD project failures can be expensive and have dire consequences on organizational performance [22]; moreover, ISD projects involve knowledge-intensive tasks that must be performed by highly skilled team members [61]. It is important to reach beyond management of contracts and move toward management of relationships.…”
Section: Implications For Researchmentioning
confidence: 99%
“…Prior research indicates that this inability may arise if the official IT unit lacks resources (Winkler & Brown, 2014), business knowledge (Tiwana, 2009;Winkler & Brown, 2013), openness and honesty (Nwankpa & Roumani, 2014), or agility (see Györy et al, 2012). Thus, the central IT "refuses" to act.…”
Section: Shadow Systems Affect Power Relations In Organizationsmentioning
confidence: 99%